(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The COVID-19 pandemic really highlighted some serious weaknesses in how businesses operate around the globe, particularly for Small and Medium Enterprises (SMEs) in emerging markets like Nigeria. A lot of these SMEs faced major challenges, including supply chain disruptions, financial setbacks, workforce issues, and a drop in consumer demand. As we move into the post-COVID world, it’s become clear that building organizational resilience is crucial for both sustainability and growth. This research dived into how strategic leadership and innovation can be harnessed to boost the resilience of SMEs in Nigeria's changing economic environment. It looks at various leadership practices, the adoption of innovative solutions, risk management tactics, and flexible business models that SMEs are using to tackle the challenges that have arisen after the pandemic. The study employed a mixed-methods approach, combining quantitative surveys with qualitative interviews to gather rich insights from SME owners, managers, and employees. This research took place in Kano and Plateau States, two vital economic hubs in Northern Nigeria that boast a variety of thriving small and medium-sized enterprises (SMEs). This study selected 25 SMEs, interviewing one or two key informants from each, such as CEOs, heads of innovation, or HR managers. This study used purposive sampling technique to pinpoint SMEs that fit our inclusion criteria and have shown some level of strategic adaptation during or after the COVID-19 pandemic. This study analysed the interview transcripts using thematic analysis. This study used simple linear regression analysis facilitated by SPSS version 28. The findings demonstrate that strategic leadership, innovation, and organizational challenges each play an important role in strengthening organizational resilience. Strategic leadership showed a significant positive effect on organizational resilience, indicating that organizations with visionary, proactive, and adaptive leaders are better equipped to withstand disruptions and maintain stable performance. Innovation also had a strong and positive impact on resilience, suggesting that organizations that consistently invest in new ideas. Organizations should implement continuous leadership development programs focusing on decision-making, crisis management, and strategic foresight. Organizations should allocate a fixed annual budget for research, technology upgrades, and new product or service development. Leaders should conduct regular environmental scanning and risk assessments to better understand emerging challenges and respond proactively.